Dynamics via measurability - Svetlana Butler; Joseph Rosenblatt (Abstract and Applied Analysis)
Generators f for σ-algebras can be used to view the dynamics of an invertible measurable transformation T in terms of the range values of f∘T. Such generators are the norm rather than the exception. Related measurable and quantitative methods of estimating a function from the behavior of ergodic averages are also discussed.